2004
DOI: 10.1186/1471-2431-4-20
|View full text |Cite
|
Sign up to set email alerts
|

Morphine for elective endotracheal intubation in neonates: a randomized trial [ISRCTN43546373]

Abstract: BackgroundElective endotracheal intubations are still commonly performed without premedication in many institutions. The hypothesis tested in this study was that morphine given prior to elective intubations in neonates would decrease fluctuations in vital signs, shorten the duration of intubation and reduce the number of attempts.MethodsFrom December 1999 to September 2000, infants of all gestations admitted to a level III neonatal intensive care unit and requiring an elective endotracheal intubation were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 17 publications
3
76
0
1
Order By: Relevance
“…At the time when the study was designed, the dose was chosen to meet the clinical need for a semiurgent intervention referring to a previous study that showed that a moderately high dose of morphine, 0.2 mg/kg, had no positive effects as compared with placebo (25). In our trial, additional doses of morphine, 0.15 mg/kg, were administered in both randomization groups as indicated according to validated pain scales.…”
Section: Discussionmentioning
confidence: 99%
“…At the time when the study was designed, the dose was chosen to meet the clinical need for a semiurgent intervention referring to a previous study that showed that a moderately high dose of morphine, 0.2 mg/kg, had no positive effects as compared with placebo (25). In our trial, additional doses of morphine, 0.15 mg/kg, were administered in both randomization groups as indicated according to validated pain scales.…”
Section: Discussionmentioning
confidence: 99%
“…Fast-acting opioids, such as fentanyl (152)(153)(154), are probably more appropriate than morphine (155,156). Despite encouraging results, the paucity of available data for alfentanil (157) and remifentanil (119,158) imposes limitations on the use of these drugs.…”
Section: Practical Recommendations For Endotracheal Intubationmentioning
confidence: 99%
“…There was no effect on the severity of physiologic disturbances during intubation including the duration of severe hypoxemia, incidence of bradycardia, and change in mean blood pressure. 26 This lack of effect is thought to be because of the delayed onset of action of morphine 27 related to the relative hydrophilic nature of the drug. Intravenous morphine has a mean onset of action at 5 minutes and peak effect at 15 minutes.…”
Section: Analgesiamentioning
confidence: 99%